Sistem Informasi Manajemen Layanan Akademik Sekolah Berbasis Web pada SMA Negeri 2 Kodi Utara - Mensiana Guna Hari; Vinsensius Aprila Kore Dima; Paulus Mikku Ate (Router : Jurnal Teknik Informatika dan Terapan, 2025)
The Web-Based Academic Service Management Information System at SMA Negeri 2 Kodi Utara was developed to improve the effectiveness and efficiency of academic data management at the school. Currently, academic data management, including grade input, class schedules, teacher information, and academic reports, is still done manually, often causing delays and potential errors in recording. This study aims to design and create a web-based information system that can assist educational institutions in managing academic services in an integrated and real-time manner. The software development method used is the Waterfall model, which includes the phases of needs analysis, system design, implementation, testing, and maintenance. The programming language used is PHP with a MySQL database system. The result of this study is an academic management information system that can facilitate various academic activities, such as managing student data, teacher data, grades, class schedules, and academic reports. This system also makes it easier for teachers to input grades and provides fast and accurate access to academic information for students and the principal. With this system, the academic administration process at SMA Negeri 2 Kodi Utara becomes more organized, efficient, and transparent.